Channa Striatus Protects Against PTZ-Induced Seizures in LPS Pre-conditioned Zebrafish Model - Lee, Vanessa Lin Lin; Norazit, Anwar; Noor, Suzita Mohd; Shaikh, Mohd. Farooq (Frontiers in Pharmacology, 2022)
Epilepsy is a neurological disorder characterized by recurrent unprovoked seizures. Mounting evidence suggests the link between epileptogenesis and neuroinflammation. We hypothesize that eliminating neuroinflammation can alleviate seizure severity and prolong seizure onset. Channa striatus (CS) is a snakehead murrel commonly consumed by locals in Malaysia, believed to promote wound healing and mitigate inflammation. This study aims to unravel the anticonvulsive potential of CS extract on neuroinflammation-induced seizures using an adult zebrafish model. Neuroinflammation was induced via cerebroventricular microinjection of lipopolysaccharides from E. coli and later challenged with a second-hit pentylenetetrazol at a subconvulsive dose of 80 mg/kg. Zebrafish behaviour and swimming pattern analysis, as well as gene expression analysis, were done to study the pharmacological property of CS. CS extract pre-treatment in all doses significantly reduced seizure score, prolonged seizure onset time and slightly improved the locomotor swimming pattern of the zebrafish. CS extract pre-treatment at all doses significantly reduced the expression of NFKB gene in the brain, and CS extract at 25 mg/L significantly reduced the IL-1 gene expression suggesting anti-neuroinflammatory properties. However, there were no significant changes in the TNFα. Besides, CS extract at 50 mg/L also elevated the expression of the CREB gene, which exerts neuroprotective effects on the neurons and the NPY gene, which plays a role in modulating the inhibition of the excitatory neurotransmission. To sum up, CS extract demonstrated some anticonvulsive and anti-inflammatory activity on neuroinflammation-induced seizures. Still, more studies need to be done to elucidate the mechanism of action of CS extract.